Unleashing the growth potential of Indian MSME sector - Sumanjeet Singh; Minakshi Paliwal (Comparative Economic Research. Central and Eastern Europe, 2017)
The MSME sector occupies a position of strategic significance in the Indian economic structure. This sector contributes nearly eight per cent to country's GDP, employing over 80 million people in nearly 36 million widely-dispersed enterprises across the country; accounting for 45 per cent of manufactured output, 40 per cent of the country's total export, and producing more than 8000 valueadded products ranging from traditional to high-tech. Furthermore, these enterprises are the nurseries for innovation and entrepreneurship, which will be key to the future growth of India. It is also an acknowledged fact that this sector can help realise the target of the proposed National Manufacturing Policy to enhance the share of manufacturing in GDP to 25 per cent and to create 100 million jobs by the end of 2022, as well as to foster growth and take India from its present two trillion dollar economy to a 20 trillion dollar economy. Despite the sector's high enthusiasm and inherent capabilities to grow, its growth story still faces a number of challenges. In this light, the present paper examines the role of Indian MSMEs in India's economic growth and explores various problems faced by the sector. The paper also attempts to discuss various policy measures undertaken by the Government to strengthen Indian MSMEs. Finally, the paper proposes strategies aimed at strengthening the sector to enable it to unleash its growth potential and help make India a 20 trillion dollar economy.
Keywords: L25; L26; J2; M14; M48; 330; MSMEs; Competitiveness; Growth; India